Influenza vaccine uptake among at-risk adults (aged 16-64 years) in the UK: a retrospective database analysis - Simon Oakley; Julien Bouchet; Paul Costello; James Parker (BMC, 2021)
Abstract Background In the UK, annual influenza vaccination is currently recommended for adults aged 16-64 years who are in a clinical at-risk group. Despite recommendations, rates of vaccine uptake in the UK have historically been low and below national and international targets. This study aims to analyse vaccine uptake among adults in clinical at-risk groups from the 2015-2016 influenza season to the present. Methods A retrospective analysis of influenza vaccine coverage in the UK was conducted using data extracted from publicly available sources. Clinically at-risk individuals (as defined by Public Health England), including pregnant women, aged 16-64 years, were included in this study. Results Influenza vaccination coverage rates across the UK in adults aged 16-64 years in a clinical at-risk group have been consistently low over the past 5 years, with only 48.0, 42.4, 44.1 and 52.4% of eligible patients in England, Scotland, Wales and Northern Ireland receiving their annual influenza vaccination during the 2018-2019 influenza season. Influenza vaccine coverage was lowest in patients with morbid obesity and highest in patients with diabetes in 2018-2019. Coverage rates were below current national ambitions of ≥75% in all clinical risk groups. In these clinical at-risk groups, influenza vaccine coverage decreased between 2015 and 2019, and there was considerable regional variation. Conclusions Uptake of the influenza vaccine by adults aged 16-64 years in a clinical at-risk group was substantially below the national ambitions. As a result, many individuals in the UK remain at high risk of developing severe influenza or complications. Given that people who are vulnerable to COVID-19 are also at increased risk of complications from influenza, during the 2020-2021 season, there is a heightened need for healthcare professionals across the UK to address suboptimal vaccine uptake, particularly in at-risk patients. Healthcare professionals and policymakers should consider measures targeted at increasing access to and awareness of the clinical benefits of the influenza vaccine.